2020
DOI: 10.1177/0363546520946101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Posterior Glenoid Bone Loss and Retroversion on Arthroscopic Posterior Glenohumeral Stabilization

Abstract: Background: Posterior glenohumeral instability is an increasingly recognized cause of shoulder instability, but little is known about the incidence or effect of posterior glenoid bone loss. Purpose: To determine the incidence, characteristics, and failure rate of posterior glenoid deficiency in shoulders undergoing isolated arthroscopic posterior shoulder stabilization. Study Design: Cohort study; Level of evidence, 3. Methods: All patients undergoing isolated posterior labral repair and glenoid-based capsulor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 40 publications
(50 reference statements)
1
48
0
Order By: Relevance
“…Risk factors for recurrence of posterior instability include age <40 years at the first instability event, dislocation due to seizure, large reverse Hill-Sachs lesion, and increased glenoid retroversion. 5,29,35 Several studies have shown a relationship between glenoid bone loss and increased risk of recurrent instability after posterior labral repair 4,41 ; however, glenoid bone loss has not been shown to be a risk factor in other studies. 9,20 Whereas for anterior instability there is a generally well-accepted understanding of the critical amount of glenoid bone loss at which capsulolabral repair alone would not be sufficient, 3,11,12,24,36,37 this is not the case for posterior instability.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors for recurrence of posterior instability include age <40 years at the first instability event, dislocation due to seizure, large reverse Hill-Sachs lesion, and increased glenoid retroversion. 5,29,35 Several studies have shown a relationship between glenoid bone loss and increased risk of recurrent instability after posterior labral repair 4,41 ; however, glenoid bone loss has not been shown to be a risk factor in other studies. 9,20 Whereas for anterior instability there is a generally well-accepted understanding of the critical amount of glenoid bone loss at which capsulolabral repair alone would not be sufficient, 3,11,12,24,36,37 this is not the case for posterior instability.…”
mentioning
confidence: 99%
“…9,20 Whereas for anterior instability there is a generally well-accepted understanding of the critical amount of glenoid bone loss at which capsulolabral repair alone would not be sufficient, 3,11,12,24,36,37 this is not the case for posterior instability. One study showed that the critical amount of posterior glenoid bone loss was >13.5%, 41 and a biomechanical model suggested that bony augmentation would be necessary with >20% of posterior glenoid bone loss. 27 Despite this, the natural history of posterior glenoid bone loss and its role in the surgical management of posterior glenohumeral instability remain poorly understood.…”
mentioning
confidence: 99%
“…Given the intra-articular establishment of 2 suture anchors in the glenoid cavity for capsular closure, proper portal placement must be ensured to avoid unnecessary glenoid bone loss. In a 2020 study of patients undergoing arthroscopic posterior glenohumeral stabilization procedures, Wolfe et al 21 found that patients with moderate posterior glenoid bone deficiency had a significantly higher rate of reoperation (P ¼ .024), had increased glenoid retroversion (P ¼ .01), had instability instead of pain on initial presentation (P < .001), and had positive jerk test results (P ¼ .01). Furthermore, in a 2018 study of patients who underwent arthroscopic isolated stabilization of the posterior labrum at a single military treatment facility, Hines et al 22 showed those with subcortical bone loss greater than 13.5% were statistically less likely to return to full duty.…”
Section: Disadvantagesmentioning
confidence: 99%
“…See related article on page 551 P osterior shoulder instability is an increasingly recognized pathologic condition of the shoulder. [1][2][3][4][5] It is commonly observed in young collision and overhead athletes, especially with flexion, external rotation, overhead and forward pressing, and pushing activities. Cognetti, Hughes, Kay, Chasteen, Fox, Hartzler, Lin, and Sheean should be congratulated for their Level IV systematic review, "Bone Block Augmentation of the Posterior Glenoid for Recurrent Posterior Shoulder Instability Is Associated With High Rates of Clinical Failure."…”
mentioning
confidence: 99%
“…6 There is a continued and persistent problem in the setting of posterior instability when there is significant posterior retroversion, whether it is either acquired or congenital. 2,7,8 This is the usual case in which a posterior bone block is used; however, the outcomes have been mixed, at best. 6,[9][10][11] While arthroscopic capsulolabral repair remains the mainstay of treatment in refractory cases for posterior instability, associated postoperative complications can still occur.…”
mentioning
confidence: 99%